ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK MINERAL BUKAN LOGAM DAN BATUAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) PADA BADAN KEUANGAN KABUPATEN MINAHASA UTARA - Mowoka, Reza Gerry Barten; Manossoh, Hendrik; Gerungai, Natalia (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Internally generated revenue is an income derived from the sources within its own territory which is collected according to local regulations in accordance with the regulation of applicable constitutions. This research is organize to find the level of effectiveness and the contribution tax of non-metallic minerals and stones as source of PAD in North Minahasa Regency. The tax of non-metallic minerals and stones is a tax of non-metallic minerals and stones activities that taken from the earthâs natural resources from inside and outside. The survey method past in this survey is descriptive qualitative. The results show that the effectiveness of non-metallic minerals and stones taxes in 2014-2017 are âvery effectiveâ and the highest effectiveness is in 2017 with the percentage 116.14%. Meanwhile, the non-metallic minerals and stones taxes contribution in the past four years rated with under maximum, so it is included in the âvery lessâ criteria of contribution. However, the collection system that must be constantly monitored and be noticed in order to receive the taxes of non-metallic minerals and stones in controlled and remain highly still effective.Keywords: Internally Generated Revenue, Tax of Non-Metallic Minerals and Stones, Effectiveness, Contribution, Local Tax